The Temperature Compensation of FBG Sensor for Monitoring the Stress on Hole-Edge - Feifei Ren; Weifang Zhang; Yingwu Li; Yudong Lan; Yukuan Xie; Wei Dai (IEEE Photonics Journal, 2018)
To apply Fiber Bragg Grating (FBG) sensors in the hole structural health monitoring of aircraft, this study investigates a temperature compensation algorithm based on Fourier curve-fitting, combined with an analysis of FBG layout. The results identify that the wavelengths have a linear relationship with stress and temperature and the linear correlation coefficients are all greater than 0.9. In the experiment, the temperature range was 17 °C–100 °C (step is 10 °C) and the tensile force changed from 0 N to 10 KN (step is 1 KN). With the Fourier curve-fitting of the wavelength variation, the temperature compensation can be actualized, and the average error of temperature is 0.17 °C. By integrating the algorithm in the self-developed FBG interrogation system, the real-time monitoring of stress is achieved with the average error of stress is 3.9 μϵ.